PELESTARIAN HUTAN MANGROVE MELALUI PENDEKATAN MINA HUTAN (SILVOFISHERY) - Kusno Wibowo (Jurnal Teknologi Lingkungan, 2006)
Indonesia contains about one-third of the world’s total mangroves areas,but experts say more than half of the country’s mangrove forest havebeen destroyed since the 1940s. The main sustainable alternatives tocoastal aquaculture pond development within or associated withmangrove are silvofisheries and mariculture. Silvofishery is a form ofintegrated mangrove tree culture with brackish water aquaculture. Thisintegrated approach to conservation and utilization of the mangroveresource allows for maintaining a relatively high level of integrity in themangrove area while capitalizing on the economic benefits of brackishwater aquaculture. Traditional models of silvofishery is the Empang Paritmodel, which is sometimes reffered to as Tambak Tumpangsari, wasdeveloped in Indonesia, tracing its roots back perhaps over a thousandyears. The modern version of Empang Parit is today being promoted bythe Indonesian Ministry of Foretry and the Directorate General ofFisheries. Silvofisheries have been successfully developed in Indonesiasuch as in Sinjai (Sulawesi), Cikeong (West Java), Pemalang (CentralJava), and Bali.